Recruiting mechanisms used by sex trafficking networks in Nevada, United States - Andrade-Rubio, Karla Lorena (Universidad Autónoma de Tamaulipas, 2020)
The international sex trade, involving young people who are taken from Central America and Mexico to the United States, has been widely documented. However, it remains a serious problem, from which its changing dynamics and recruitment strategies, whether voluntary or forced, are unknown. The objective of this paper was to examine the mechanisms used by sex smuggling networks to recruit migrant women to be prostituted in Nevada, USA. This research is based on a qualitative methodology that includes interviews with 3 Central American recruiters and 12 women from Mexico and Central America. The main results indicate that these networks recruit predominantly vulnerable underage girls with a past associated with prostitution and towering economic necessities. Recruitment mechanisms used by these networks are not based on the use of violence, but on the abuse of a position of vulnerability. In conclusion, not resorting to violent recruitment strategies reduces the risk of this activity, since women do not report them because they do not consider themselves victims.